Educational Innovation in Economics and Business V : Business Education for the Changing Workplace - Borghans, L.; Gijselaers, W.; Milter, Richard G.; Stinson, John E. (Educational innovation in economics and business ;, 2002)
The Information and Communication Technology revolution results in profound changes to the heart of business and economics. Changes in the workplace, new communication technology, new organizational structures, and new production technologies force business educators to renew their focus on the curricula of business schools. There is no doubt these changes influence business education and instructional technology. But change will go far beyond the mere introduction of technology in the classroom. Alliances between the corporate world and business education are no longer fictitious but are necessary to establish stronger bonds between educational systems and the workplace. The fifth volume in the series Educational Innovation in Economics and Business contains a unique selection of articles addressing various issues on how business education should adapt to changing needs of the corporate world. It is meant for educators in corporate training centers, and for teachers in further and higher education.